Comparison of FOB-USP standard cephalometric analysis in Caucasian, Black, Japanese, Afro-Caucasian, and Japanese Caucasian individuals - Soviero, Laura Dias (2024)
Introduction: Cephalometry is a tool used to measure head dimensions through lateral radiography; however, most cephalometric analyses were developed based on white individuals, which may be inadequate for people of other ethnicities. Considering the significant racial heterogeneity in Brazil resulting from colonization and immigration, professionals should consider the facial peculiarities of each race to individualize orthodontic planning and treatment. Objective: Compare five racial groups in the Brazilian population using the FOB-USP standard cephalometric analysis. Methods: A sample of 215 lateral radiographs of young Brazilians with normal occlusion was used. Individuals were divided into five groups (Caucasian, Black, Japanese, Afro-Caucasian, and Japanese-Brazilian) according to their ancestry. Cephalometric tracings and measurements were performed using the FOB-USP standard cephalometric analysis. Results: The SNA was greater for the Black group, and the smallest value was for the Caucasian group. The mandible demonstrated greater SNB and SND for the Black group and a significantly smaller protrusion for the Caucasian group. ANB values were greater for the Black group and smaller for the Caucasian group. Black individuals presented greater NAP and HNB than Caucasians and Japanese descendants. There were no statistically significant differences between racial groups for 1-NA and 1.NA. Black individuals exhibited greater 1-NB, 1.NB, and IMPA compared to other racial groups. The variables 1.NB and IMPA showed a similar inclination for the Caucasian and Japanese groups. Dental measurements presented intermediate values between Caucasians and Blacks for the Afro-Caucasian group, and between Caucasians and Japanese for Japanese-Caucasian individuals. Conclusion: The studied groups present cephalometric differences and racial characteristics that should be considered in orthodontic planning.